Numerical study of conjugate natural convection heat transfer of a blood filled horizontal concentric annulus - Alsabery, Ammar I.; Naganthran, Kohilavani; Azizul, Fatin M.; Hashim, Ishak; Nazar, Roslinda (International communications in heat and mass transfer, 2020)
A numerical investigation is accomplished on the natural convection flow and heat transfer in a horizontal concentric annulus in the presence of cylindrical solid wall and Carreau non-Newtonian blood model. The inner circular surface of the cavity is heated to a constant temperature and the outer circular surface is cooled. The boundaries of the annulus are assumed to be impermeable, the fluid within the cavity is assumed to be non-Newtonian blood when the Boussinesq approximation is applicable. The Galerkin weighted residual method is applied numerically to solve the dimensionless governing equations subject to the boundary conditions. The numerical results explained in the form of streamlines, isotherms, local and average heat transfer with variation of the Rayleigh number, Prandtl number, power-law index and the thermal conductivity of the cylindrical solid wall within the range of (103 ≤ Ra ≤ 106), (5 ≤  Pr  ≤ 50), (0.2 ≤ n ≤ 0.8) and (0.25 ≤ kw ≤ 1.45), respectively. Validations with experimental/numerical data are accomplished which provide a clear conviction to the numerical data of the existing code. It has been found that a low power-law index improves the fluid flow and increases the rate of heat transfer.